(untitled) (Bangladesh Agronomy Journal, 2020)
Quality is one of the key characteristics of rice and is largely governed by nitrogen application. An experiment was conducted to scrutinize the effect of nitrogen on quality characteristics of rice, with three nitrogen levels (viz. 50 kg N ha-1, 100 kg N ha-1 and 150 kg N ha-1) and four varieties/lines (viz. SAU ADL1, BRRI dhan70, BRRI hybrid dhan6 and SAU ADL11). Results revealed that quality characters of transplanted Aman rice were significantly influenced by nitrogen, variety and their interaction. Increasing trend was observed with the increasing level of nitrogen from 50 to 150 kg ha-1 regarding hulling percentage and milling outturn while decreasing trend was observed in case of apparent amylose content and imbibition ratio. Maximum protein content (9.60%) and gel consistency (96.16 mm) were recorded at 100 kg N ha-1. Among the studied materials, SAU ADL11 performed better in case of all studied parameters. Although interaction of 150 kg N ha-1 with SAU ADL1 and SAU ADL11 gave maximum value of hulling percentage and milling outturn. In interaction of 100 kg N ha-1 with these two lines gave maximum protein, gel consistency and satisfactory levels of all quality characters. So, it can be suggested to carry out further investigation with these two rice lines having 100 kg N ha-1. Bangladesh Agron. J. 2020, 23(1): 59-66